Studi Komparatif Gotong Royong dan Bastazete: Peran Gereja Lokal dalam Mengatasi Kemiskinan di Kepulauan Nias - Fioli; Harlinton Simanjuntak; Anastasya Laoli (Jurnal Teologi Pambelum, 2026)
Poverty in Indonesia, particularly in Nias, is a complex issue related to access to education, unemployment, and access to the workforce. These four aspects are interrelated, forming a complex cycle that is difficult to break. This study aims to identify the role of the local church in poverty alleviation in Nias through the integration of Christian values, particularly based on the principle of bastazete in Galatians 6:2, with the culture of mutual cooperation that is deeply rooted in Indonesian society. A comparative theological-anthropological study has never been conducted before, creating an opportunity to explore how the integration of theology and anthropology can drive the church's role in addressing social issues within society. Using a comparative-integration approach, this study found that the local church in Nias has strategic potential to become an agent of change through education and community empowerment programmes based on Christian values and the culture of mutual cooperation. This integration not only offers practical solutions to poverty but also strengthens the role of the church in the local and even global context. Practically, this research contributes conceptual frameworks for local churches to become agents of change through theological and practical approaches.